2021
DOI: 10.12968/jpar.2021.13.8.332
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of ethical dilemmas in Australian paramedicine

Abstract: Background: Paramedics experience a range of ethical dilemmas in the course of their work. To date, ethical dilemmas by Australian paramedics have not been documented. With the scope of practice becoming increasingly complex, paramedic education may not have evolved to meet holistic professional demands. Aim: To describe the ethical dilemmas experienced by contemporary Australian paramedics. Methods: An online survey, based on a previous instrument, was used to explore a range of ethical dilemmas. Findings: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Diversity is not only experienced through their clinical caseload, but also across cultural contexts and in geographically disparate settings, from metropolitan locations through to regional and remote sites (Hartley, 2012 ; O'Meara & Duthie, 2018 ). The cases attended by paramedics can present a range of ethical dilemmas, including but not limited to refusal of service, the protection of vulnerable persons, resuscitation decisions, and challenges involving advance care directives (Adams et al, 1992 ; Heilicser et al, 1996 ; Moore, 2020 ; Moritz et al, 2020 ; Nordby & Nøhr, 2012 ; Shearer et al, 2021 ). In the past, paramedics have articulated the need for improved ethics education to assist them in dealing with the ethical problems faced (Heilicser et al, 1996 , p. 242).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity is not only experienced through their clinical caseload, but also across cultural contexts and in geographically disparate settings, from metropolitan locations through to regional and remote sites (Hartley, 2012 ; O'Meara & Duthie, 2018 ). The cases attended by paramedics can present a range of ethical dilemmas, including but not limited to refusal of service, the protection of vulnerable persons, resuscitation decisions, and challenges involving advance care directives (Adams et al, 1992 ; Heilicser et al, 1996 ; Moore, 2020 ; Moritz et al, 2020 ; Nordby & Nøhr, 2012 ; Shearer et al, 2021 ). In the past, paramedics have articulated the need for improved ethics education to assist them in dealing with the ethical problems faced (Heilicser et al, 1996 , p. 242).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, paramedics have articulated the need for improved ethics education to assist them in dealing with the ethical problems faced (Heilicser et al, 1996 , p. 242). There have been few studies addressing this need; however, recent research has revealed that paramedics rely more on experience than education to resolve ethical dilemmas (Shearer et al, 2021 , p. 336). This is problematic as students of paramedicine have limited opportunities to gain clinical experience underscoring the need to rely on education to provide the theoretical knowledge and skills underpinning good ethical decision making for paramedics.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are reflected in the expanding body of research from the educational systems for both paramedics [60,175,206,207] and RNs [9,13,40,41,55], where a greater focus on non-technical cognitive skills in the educational programmes and in the training of AS professionals were requested. Non-technical cognitive skills in the AS have been suggested as consisting of a wide range of associated concepts, for example, situational awareness, clinical reasoning, problem-solving, clinical decision-making, communication, empathy, caring, altruism, leadership, teamwork, ethics, and interpersonal skills as fundamental parts of the competencies needed [33,60,175,176,182,206,208].…”
Section: Ethical Dimensions Of Clinical Decision-makingmentioning
confidence: 99%
“…This tension between different values in professional decision-making traditions, such as the AS, has also been referred to as "paradoxes", which creates a "professional room" in which professional judgement and phronetic action are needed [37]. These situations in the AS have been found to be on the increase and concern, for example, situations of conveyance or non-conveyance [29,30,211], patients with reduced decisional capacity [54,207], contradictions between medical guidelines and patient needs [33], conflicting perspectives on patient needs between the professionals, the patient, and their relatives [54,207], palliative and end-of-life care encounters [207], diverging perspectives on caring objectives in the AS team [34], refusal of service [207], and a perceived misuse of health care resources [19,24,30].…”
Section: Paradoxes As a Basis For Professional Judgementmentioning
confidence: 99%
See 1 more Smart Citation